Systematic Literature Review on Crime Prediction using Machine Learning Techniques - Esan, Omobayo; Bester Chimbo (AI Society & STMIK Indonesia, 2025)
Abstract contains problem statement, approaches/problem solving method, objectives and resulTo lower the crime rate in the community, many governments around the world have made preventive security measures their top priority. Thus, a major and extensively studied field is the use of machine learning in crime prediction. To investigate crime prediction using machine learning approaches, this study carried out a systematic literature review. The review assesses performance evaluation criteria, forecast methods, present issues, and potential future directions. From 2018 to 2024, a total of 100 research papers covering machine learning techniques for crime prediction were reviewed. The supervised learning approach is the most often used crime prediction technology, according to the review. The evaluation and performance criteria, the tools used to construct the models, and the difficulties they face in predicting crime were also covered. Machine learning approaches for crime prediction are an interesting area of research, and academics have used a number of machine learning models.